PT. Tira Austenite, Tbk dan Analisis Kinerja Perusahaan Ekspedisi dalam Perspektif Supply Chain dan Metode Analytic Network Process (ANP) - Khristian Edi Nugroho Soebandrija; Rizal Herjiwandono Kartowisastro (ComTech: Computer, Mathematics and Engineering Applications, 2015)
PT. TIRA AUSTENITE, Tbk (PTATbk) and other companies in the field of supply chain require coordination pertaining cross functional and cross collaboration. The mentioned collaboration is required especially for Expedition Company. The performance analysis of Expedition Company, including PTATbk is needed to face the global competition. Company contribution generally, and in particular for Empirical Study toward PTATBK can lead to the problem solving and performance improvement, which covers selecting optimal expedition company and efficient time to dispatch product from existing route to be integrated into the core essence of this research pertaining PTATbk. The mentioned research refers to Empirical Study dan Managerial Implications through books and journals as reference in the Research Methodology. The focus of this researchmethodology is the Analytic Network Process (ANP); criteria of Price and Service; and other important criteria that support the performance analysis within PTATbk. Software ARENA Simulation plays vital role in this research that has the conclusion and recommendation toward problem solving and performance improvement that are translated into benefits versus risks and its form of % and the currency of IDR and/or USD.